Study of micro-gap reactors for pulsed electric field sterilization. (December 2015) - Guo, Jianguang; Zhao, Liping; Cao, Yi; Yu, Ronghui; Wang, Qiong; Hu, Ning; Liu, Yang; Yang, Jun
Static and continuous-flow micro-gap reactors have been designed for the sterilization of bacteria. Their performances were verified using some pulsed electric fields. Several parameters such as electric field strength, pulse number and width, as well as flow rate, which may impact the sterilization effect, have been experimentally evaluated on these devices. Experimental results showed that the strength and width of pulses had significant impacts on the sterilization. Stronger and wider pulses favored the sterilization. More pulses could also achieve better sterilization effect. Continuous-flow manipulation contributed to realize high-efficiency sterilization. However, flow rate should be lower than a critical value. Higher flow rate may reduce the residence time in the reactor and harm the sterilization effect. Micro-gap reactor between the two parallel plate electrodes can contain more solution and the sample can be manipulated in a continuous way to realize higher sterilization throughput, but it is sometimes difficult to form even gap between these plate electrodes. Rough surface or burrs on these electrodes may induce discharge and limit the electric field strength. Some coatings on their surface may decrease the discharge, but they also undermine the electric field.